2006
DOI: 10.1164/rccm.200603-402oc
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Therapy in Patients with Chronic Sarcoidosis and Pulmonary Involvement

Abstract: Infliximab therapy resulted in a statistically significant improvement in % predicted FVC at Week 24. The clinical importance of this finding is not clear. The results of this Phase 2 clinical study support further evaluation of anti-TNF-alpha therapy in severe, chronic, symptomatic sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
329
3
23

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(369 citation statements)
references
References 36 publications
14
329
3
23
Order By: Relevance
“…Some experts advocate 6-12 mo of therapy, whereas others recommend consideration of lifelong treatment because of reports of relapse or sudden death. 83,84 Other immunosuppressive therapies, such as methotrexate, azathioprine, mycophenolate mofetil, or infliximab, have been used with some success for systemic sarcoidosis, [85][86][87][88][89][90][91] but data regarding their use in CS are quite limited.…”
Section: Management Of Cs Immunologic Therapymentioning
confidence: 99%
“…Some experts advocate 6-12 mo of therapy, whereas others recommend consideration of lifelong treatment because of reports of relapse or sudden death. 83,84 Other immunosuppressive therapies, such as methotrexate, azathioprine, mycophenolate mofetil, or infliximab, have been used with some success for systemic sarcoidosis, [85][86][87][88][89][90][91] but data regarding their use in CS are quite limited.…”
Section: Management Of Cs Immunologic Therapymentioning
confidence: 99%
“…ETA was assessed in a preliminary trial of patients with progressive sarcoidosis, but the trial was stopped because of treatment failure in majority of participants [77]. A more recent phase 2 clinical trial using INF showed a statistically significant improvement in % predicted FVC at week 24, supporting further evaluation of anti-TNF therapy for sarcoidosis [78].…”
Section: Neurological Inflammation-elevatedmentioning
confidence: 99%
“…Anti-TNF monoclonal antibody therapy has been used successfully in granulomatous inflammatory diseases including Crohn's and adult sarcoidosis (11). In our experience, the administration of anti-TNF agents allowed better disease control with tapering of systemic cortico-steroids.…”
Section: Discussionmentioning
confidence: 86%